MULTI-MODAL EMOTION RECOGNITION MODEL USING GENERATIVE ADVERSARIAL NETWORKS (GANs) FOR AUGMENTING FACIAL EXPRESSIONS AND PHYSIOLOGICAL SIGNALS - Hegh, Abya Newton; Adeyelu, Adekunle Adedotun; Iorliam, Aamo; Otor, Samera U. (FUDMA JOURNAL OF SCIENCES, 2025)
Emotion recognition is a critical area of research with applications in healthcare, human-computer interaction (HCI), security, and entertainment. This study addressed the limitations of single-modal emotion recognition systems by developing a multi-modal emotion recognition model that integrates facial expressions and physiological signals, enhanced by Generative Adversarial Networks (GANs). It aims at improving accuracy, reliability, and robustness in emotion detection, particularly underrepresented emotions. The study utilized the FER-2013 dataset for facial expressions and the DEAP dataset for physiological signals. GANs were employed to augment datasets, address class imbalances and enhance feature diversity. A hybrid multi-modal model was developed, combining Convolutional Neural Networks (CNNs) for facial expression recognition and Long Short-Term Memory (LSTM) networks for physiological signal analysis. Hybrid fusion was used to integrate features at multiple levels, maximizing the complementary strengths of each modality. The results demonstrate significant improvements in emotion recognition. Without GAN augmentation, the CNN and LSTM models achieved accuracies of 62% and 76%, respectively. The hybrid model outperformed, gaining 90% across all metrics. With GAN-augmented datasets, the CNN and LSTM models improved to 81% and 86%, respectively, while the hybrid (multi-modal) model achieved state-of-the-art performance with 93% accuracy and an F1-score of 92%. These findings underscore the efficacy of GANs in enhancing data diversity and the advantages of multi-modal integration for robust emotion recognition. The study contributes to knowledge by introducing a GAN-augmented hybrid multi-modal framework, advancing methodologies in emotion recognition. Recommendations for future work include addressing ethical considerations in emotion recognition systems.